2023
DOI: 10.1111/php.13833
|View full text |Cite
|
Sign up to set email alerts
|

The copious photochemistry of 2,6‐diaminopurine: Luminescence, triplet population, and ground state recovery*

Abstract: Abstract9H‐ and 7H‐2,6‐Diaminopurine (26DAP) photoinduced events in vacuum were studied at the MS‐CASPT2/cc‐pVDZ level of theory. The S1 1(ππ* La) state is initially populated evolving barrierless towards its minimum energy structure, from where two photochemical events can take place in both tautomers. The first is the return of the electronic population to the ground state via the C6 conical intersection (CI‐C6). The second involves an internal conversion to the ground through the C2 conical intersection (CI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 52 publications
2
1
0
Order By: Relevance
“…Similar energy barriers of 0.4 eV to access the C2-CI and of 0.05 eV to access the C6-CI were obtained for the N9H tautomer of 2,6DAP in water at the TD-BP86/CPCM/def2-TZVP//TD-B3LYP/CPCM/cc-pVDZ level of theory. 15 In vacuum, Oliveira et al 53 reported upper-limit energy barriers of 0.83 and 0.57 eV to access the C2-CI and C6-CI from the S1(ππ* La) minimum at the MS(3)-CASPT2 (14,11)/cc-pVDZ level of theory, which are in qualitative agreement with those reported in this study in MeCN. Therefore, the calculations predict that the S1(ππ* La) state population should decay significantly faster to the ground state through the C6coordinate than through the C2-coordinate both in solution and in the gas phase.…”
Section: Statesupporting
confidence: 90%
See 1 more Smart Citation
“…Similar energy barriers of 0.4 eV to access the C2-CI and of 0.05 eV to access the C6-CI were obtained for the N9H tautomer of 2,6DAP in water at the TD-BP86/CPCM/def2-TZVP//TD-B3LYP/CPCM/cc-pVDZ level of theory. 15 In vacuum, Oliveira et al 53 reported upper-limit energy barriers of 0.83 and 0.57 eV to access the C2-CI and C6-CI from the S1(ππ* La) minimum at the MS(3)-CASPT2 (14,11)/cc-pVDZ level of theory, which are in qualitative agreement with those reported in this study in MeCN. Therefore, the calculations predict that the S1(ππ* La) state population should decay significantly faster to the ground state through the C6coordinate than through the C2-coordinate both in solution and in the gas phase.…”
Section: Statesupporting
confidence: 90%
“…49 The SF approach has been used extensively to overcome the problem with the conical intersections between the ground and excited states, 38,39,50 and it has been shown to provide the correct dimensionality of the CIs. 51,52 Furthermore, we note that the conical intersections identified in this work are similar to those reported by Szabla et al, 29 and Oliveira et al, 53 at the ADC(2) and MS-CASPT2 level of theories, respectively, providing additional support for the use of SF-TD-DFT in this study.…”
Section: Statesupporting
confidence: 90%
“…In particular, the authors located C2-puckered and C6-puckered S 1 /S 0 state crossings for both tautomers, which are analogous to the C2-and C6-puckered S 1 /S 0 state crossings discussed in this work. (65) The MS-CASPT2/SA-CASSCF approach should generally offer a more accurate description of excited-state potential energy surfaces and S 1 /S 0 state crossings, particularly in the regions where the ground-state wave-function gains a highly multi-configurational character.…”
Section: Comparison Of the Scs-adc(2) Results With Previous Computati...mentioning
confidence: 99%